Enhancing Language Awareness of Student Teachers through Lesson Plan Creation - Ratih Suci Syahidah; Nani Hizriani; Hidayah Nor (LET: Linguistics, Literature and English Teaching Journal)
This research aimed to explore the challenges faced by student teachers during Teaching Practice II and examine their strategies for developing language awareness through lesson plan creation. The study employed documentation and interviews as data collection techniques, employing a qualitative case study approach for analysis. The findings revealed several challenges encountered by the students while creating their lesson plans. Firstly, in the Effective Domain, students faced difficulties in writing comprehensive lesson plans and expressed apprehension about making mistakes. Secondly, within the Power Domain, students displayed a lack of interest in identifying indicators and objectives within their lesson plans. Furthermore, in the Cognitive Domain, students encountered challenges in utilizing Bloom's Taxonomy vocabulary effectively. Lastly, within the Performance Domain, students encountered issues in structuring sentences correctly and made grammatical errors in their indicators and objectives. To develop language awareness and create appropriate lesson plans, the researchers identified five strategies employed by the students. Firstly, students needed to cultivate an awareness of natural English usage. Secondly, seeking guidance and consultation from their supervisors or teaching trainers proved beneficial. Thirdly, familiarizing themselves with the lesson plan format at the beginning of Teaching Practice II was essential. Additionally, students should revise their lesson plans based on feedback received from supervisors and teaching trainers. Finally, developing the ability to identify the taxonomies within Bloom's Taxonomy was crucial.